2000
DOI: 10.1029/1999gb900088
|View full text |Cite
|
Sign up to set email alerts
|

Intensive field measurements of nitrous oxide emissions from a tropical agricultural soil

Abstract: Abstract. The amount of nitrous oxide (N20) continues to increase in the atmosphere. Agricultural use of nitrogen fertilizers in the tropics is thought to be an important source of atmospheric N20. High frequency, highly precise measurements of the N20 flux were made with an automated system deployed in N fertilized and unfertilized agricultural plots of papaya and corn in Costa Rica for an entire corn crop growth to harvest cycle. N20 fluxes were as high as 64 ng N-N20 cm -2 h -• from fertilized versus 12 ng … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
42
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 25 publications
10
42
0
Order By: Relevance
“…Correlation analysis in the current study showed that there did not exist a significant relationship between air or soil temperatures and N 2 O emissions in P. australis community, but the significant relationship between N 2 O emissions and temperature was found in other three positions. Tang et al (2006) suggested that soil temperature did not have a strong effect on N 2 O emissions, which was consistent with results reported in tropical, agricultural soils (Crill et al, 2000;Kiese and Butterbach-Bahl, 2002). On the other hand, some studies showed that N 2 O fluxes were strongly correlated with soil temperature.…”
Section: Discussionsupporting
confidence: 80%
“…Correlation analysis in the current study showed that there did not exist a significant relationship between air or soil temperatures and N 2 O emissions in P. australis community, but the significant relationship between N 2 O emissions and temperature was found in other three positions. Tang et al (2006) suggested that soil temperature did not have a strong effect on N 2 O emissions, which was consistent with results reported in tropical, agricultural soils (Crill et al, 2000;Kiese and Butterbach-Bahl, 2002). On the other hand, some studies showed that N 2 O fluxes were strongly correlated with soil temperature.…”
Section: Discussionsupporting
confidence: 80%
“…Our study of spatial and temporal variability of trace gas fluxes forms part of a 3-year field experiment established to identify controls and to quantify dynamics of N20 fluxes from humid tropical soils under different agricultural management [Crill et al, 1999]. The time schedule for the main experiment and the variability study is given in Table 1.…”
Section: Experimental Designmentioning
confidence: 99%
“…High temporal variability of emissions from a fertilized banana plantation in Costa Rica resulted in an underestimation of mean annual N20 emissions if monthly sampled flux data are extrapolated compared to extrapolation of fluxes sampled on a fertilization event basis [Veldkamp and Keller, 1997]. Temporal variability and short-time responses of fluxes on changes in controlling factors has been demonstrated using automated sampling and analysis systems [Brumme and Beese, 1992;Crill et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plantations were abandoned about 1968 and secondary forest developed [Hartshorn, 1983;McDade and Hartshorn, 1994]. In 1994 this forest was cleared to establish farm plots for a 2-year study of nitrogen oxide fluxes from fertilized and unfertilized agricultural soils [Crill et al, 2000]. After forest clearing, papayas (Carica papaya) were planted in 1994.…”
Section: Study Areasmentioning
confidence: 99%